Application of the Joint Application Design (JAD) Method in Developing a Women's Clothing Sales Information System Website Based at Aldisa Boutique - Rima Tamara Aldisa (Westscience Press, 2024)
A website-based women's clothing sales information system is a significant solution in optimizing sales business processes and increasing market affordability for business owners. In this context, this research aims to apply the Joint Application Design (JAD) Method as an approach in developing the sales information system. The JAD method was used to actively involve stakeholders from the start of the development process, enabling a better understanding of Aldisa Boutique's business needs and user desires. Through this study, design and implement a Website-Based Women's Clothing Sales Information System by integrating the JAD method in every stage of development, including needs analysis, design and implementation. The test results show that the application of the JAD method can improve system quality by producing solutions that are more in line with user expectations and business needs. The system is expected to provide solutions for Aldisa Boutique in increasing sales efficiency and making purchases easier for consumers.